WAKAF UANG DIGITAL: POTENSI DAN TANTANGAN DALAM PENGEMBANGAN EKONOMI DI INDONESIA - Waluyo, Waluyo; Fauziah Anwar, Natasya; Maharani, Ika; Salsabila Adha, Natasya Putri (JISEF : Journal Of International Sharia Economics And Financial, 2025)
This study aims to analyze the potential and challenges of implementing digital cash waqf in economic development in Indonesia, especially in supporting the micro, small, and medium enterprises (MSMEs) sector. The method used is a literature study with a qualitative descriptive approach, reviewing literature, journals, and secondary data related to the research theme. The results of the study show that digitalization of cash waqf facilitates the process of collecting and managing funds, increasing transparency, and expanding the reach of waqf through online platforms. The collected waqf funds can be allocated productively to support MSMEs, education, health, and social infrastructure, thereby contributing to economic growth and community welfare. However, the main challenges faced include low public literacy about productive waqf, limited human resource capacity in the management institution, and regulatory constraints and trust in digital platforms. To optimize the potential of digital cash waqf, collaboration between various parties and increased public education are needed so that this innovation can become a driving force for sustainable economic development in Indonesia.